Ancient DNA suggests a historical demographic decline and genetic erosion in the Atlantic bluefin tuna - Adam Jon Andrews; Emma Falkeid Eriksen; Bastiaan Star; Kim Præbel; Antonio Di Natale; Estrella Malca; Vedat Onar; Veronica Aniceti; Gabriele Carenti; Gäel Piquès; Svein Vatsvåg Nielsen; Per Persson; et al. (Proceedings of the National Academy of Sciences, 2025)
Overexploitation has depleted fish stocks during the past century; nonetheless, its genomic consequences remain poorly understood for most species. Characterizing the spatiotemporal patterns of these consequences may provide baseline estimates of past diversity and productivity to aid management targets, help predict future dynamics, and facilitate the identification of evolutionary factors limiting fish population recovery. Here, we evaluate human impacts on the evolution of the iconic Atlantic bluefin tuna ( Thunnus thynnus ), one of the longest and most intensely exploited marine fishes, with a tremendous cultural and economic importance. We sequenced whole genomes from modern (n = 49) and ancient (n = 41) specimens dating up to 5,000 y ago, uncovering several findings. First, we identify temporally stable patterns of population admixture, as bluefin tuna caught off Norway and in the eastern Mediterranean share a greater degree of ancestry with Gulf of Mexico bluefin tuna than western and central Mediterranean bluefin tuna. This suggests that Atlantic spawning areas are important mixing grounds for the genetic diversity of Mediterranean bluefin tuna. We model effective population size to show that Mediterranean bluefin tuna began to undergo a demographic decline by the year 1900 to an extent not observed across the previous millennia. Coinciding with this, we found that heterozygosity and nucleotide diversity were significantly lower in modern (2013 to 2020) than ancient (pre-1941) Mediterranean bluefin tuna, suggesting that bluefin tuna underwent a genetic bottleneck. With this work, we show how ancient DNA provides unique perspectives on ecological complexity with the potential to inform the management and conservation of fishes.